This Study Examines the Impact of Campaign Finance Restrictions on Electoral Transparency and Integrity in ASEAN Countries - Arifin, Firdaus (Jurnal Smart Hukum (JSH), 2024)
The transparency and integrity of electoral processes are of paramount importance for the health of a democracy. They prevent corruption and ensure fairness. Many ASEAN countries have implemented strict campaign finance regulations with the aim of enhancing transparency and reducing financial influence in politics. However, the effectiveness of these policies depends on the existence of appropriate oversight mechanisms and the specific characteristics of the local political context. This research examines the impact of campaign finance restrictions on electoral transparency in ASEAN, identifies challenges, and highlights effective practices. It also offers recommendations for policy improvements. This research employs a comparative methodology and thematic analysis to examine the similarities and differences in campaign finance restrictions across the Association of Southeast Asian Nations (ASEAN). It utilises data from documents to identify policy patterns and impacts. This research examines the impact of campaign finance restrictions in ASEAN, offering new insights and data on the influence of such regulations on electoral outcomes. It also provides recommendations for enhancing transparency and integrity in elections. This article examines the efficacy of campaign finance restrictions in enhancing electoral transparency and integrity in Indonesia. The findings indicate that, despite the restrictions' objective of curbing undue influence in the electoral process, their implementation continues to encounter substantial obstacles, including inadequate oversight and a dearth of information disclosure. The research underscores the necessity for regulatory reform and the fortification of oversight mechanisms as pivotal strategies to attain elections that are more equitable and transparent.